Multiscale modeling of the low-temperature electron irradiation of beryllium - Bratchenko, M.I.; Dyuldya, S.V. (Вопросы атомной науки и техники, 2017)
Presented are the methodology and the results of the multiscale modeling of radiation defects primary production and time evolution for 2.5 MeV cryogenic (77 K) irradiation of highly deformed to ~ 10¹² cm⁻² dislocations density beryllium at the NSC KIPT electron linac ELIAS. It is shown that the application of low-temperature e⁻-irradiation of prestrained targets allows efficient suppression of vacancy-interstitial recombination due to escape of freely mi-grating self-interstitial atoms to dislocation sinks and results in abnormally high (~ 10⁻³ per atom) vacancy yield comparable with that of primarily produced Frenkel pairs at a reasonable (≤10³h)e⁻-beam exposure.